Land on fire: The spatial production of the mafia - Pearson, Lauren R (Criminology & criminal justice, 2025)
“Land on Fire: The Spatial Production of the Mafia” proposes to address a major lacuna in geographic literature: How mafia groups are socially and spatially reproducing themselves through the intentional setting of fire. Analyzing the 2021 and 2023 wildfire seasons in Sicily, this research proposes that the Sicilian Mafia is operationalizing both rural and urban space in novel ways that reflect a transformation in their organizational structure. This work engages with Henri Lefebvre’s theory on the production of space but also uses ethnography in Sicily to reorient our understanding of mafia crime, suggesting that the Sicilian Mafia’s operationalization of the landscape reflects not only an evolution of the Mafia but also an altered relationship with the land itself.